Legal Issues of Personal Data Protection and Consumer Protection in Open API Payments - Camila Amalia; Esha Gianne Poetry; Mochamad Kemal Kono; Dadang Arief Kusuma; Alex Kurniawan (Bank Indonesia, 2022)
Digital financial innovation in Indonesia demands equal disclosure of data and information between banks and financial technology (fintech) companies through the Open API. Bank Indonesia as the authority in the payment system issued a series of regulations to regulate the standardization of Open API Payments to create data disclosure integrity, as well as improve personal data protection and consumer protection in open banking. This paper will review several legal aspects that have emerged, and it will be assessed whether the current provisions have addressed a number of these legal aspects. This paper uses a normative juridical approach with a descriptive analysis specification, which uses laws and regulations as the primary material. Based on research, currently existing regulations have succeeded in addressing the legal aspects of the Open API Payment. However, to strengthen consumer rights in the Open API Payments, it is still necessary to enact a Personal Data Protection Law (PDP Law) and amend the Consumer Law that is more in favor of the interests of consumers.